ANALISIS GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA PADA BADAN PENDIDIDKAN DAN PELATIHAN (BADIKLAT) KOTA MAKASSAR - Adriani Adriani (AkMen JURNAL ILMIAH, 2013)
In this study the methods used in data collection and field is literature , the type of data using qualitative and quantitative data with methods of descriptive analysis and regression analysis . The results of this study are the leaders in the education and training bodies tend to apply a style Makassar Democratic leadership , which leadership behaviors where the position of superior and subordinate is almost the same in the company but remains on the boundary . Employees are given the freedom , and leadership styles like this always think objectively . With the largest percentage is 59.69 % , in comparison with other leadership styles are Authoritarian 19.77 % and 20.53 % Leissez Fairez . The level of job satisfaction of employees in education and training bodies Makassar qualitatively at the level of " being " . These results are based on the total score of the respondents value is in the interval 41 -45 points (assessment being) is that most 44 respondents or 36.37 % and the overall respondents . Hypothesis testing proves that there is influence of leadership style on job satisfaction of employees in education and training bodies (Badiklat) Makassar. That is, with the results of the analysis of the Pearson product moment correlation of r = 0.445 was obtained which shows the relationship of leadership style influence on employee job satisfaction is positive which is located at the bottom interval 0.40 -0559. While the coefficient determinant or the influence of leadership style on job satisfaction (r) = 0.198 Thus it can be stated that in leadership style influence on employee job satisfaction by 0.445 .